Protonated polynucleotides structures - 23. The acid-base hysteresis of poly(dG).poly(dC). - Thiele, D (1978)
The large hysteresis observed during the acid-base titration of poly(dG). poly (dC) was studied by CD and potentiometric scanning curves. Intermediate scanning loops as well as the equilibrium and metastable branches of the hysteresis loop have been determined. The potentiometric titrations showed, however, that the various complexes were not discrete entities, but were linked in "polycomplexes" as had been already suggested. This prevented a thermodynamic study of the system. The acid-base titration was further investigated as a function of ionic strength and temperature. The pK's showed considerably lower ionic strength dependence than observed for polyribonucleotide complexes. The thermal transitions permitted to establish the relative stabilities of the various complexes between pH 2.5 and pH 12.0.